A Third Musketeer on the ER: MOSPD2 is a Novel VAP-related Receptor for FFAT Motifs. (November 2018) - Di Mattia, Thomas; Tomasetto, Catherine; Alpy, Fabien
Interorganelle membrane contact sites are subcellular structures that favor exchange and communication inside the cell. Such microdomains are built by molecular bridges that create a physical connection between two distinct organelles. The field of contact sites is now flourishing with discoveries of new tethering molecules. In that context, we identified by an unbiased proteomic approach a novel scaffold protein named MOtile SPerm Domain-containing protein 2 (MOSPD2). MOSPD2 is an endoplasmic reticulum (ER)-resident protein that is able to interact with several organelle-bound proteins that possess a small motif, named FFAT (two phenylalanines in an acidic tract). Consequently, we showed that MOSPD2 and its protein partners build contacts between the ER and endosomes, mitochondria, or Golgi. These findings highlight a new way for docking organelles on the ER.